1988
DOI: 10.1038/bjc.1988.6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of c-myc and c-fos proto-oncogenes in thyroid carcinomas

Abstract: Sunmmary Tumour specimens from 23 patients with thyroid carcinoma, 22 patients with thyroid adenoma, 3 with Graves' disease, and tissues from 8 normal thyroid glands were analyzed by Southern blot hybridization for the physical state of c-myc and c-fos proto-oncogenes. In 4 patients, both the primary tumour and lymph node metastases were analyzed. No amplification or rearrangement of the two proto-oncogenes was detected. Total RNAs were also analyzed. Elevated levels of the 2.4kb c-myc RNA and of the 2.2kb c-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 31 publications
(39 reference statements)
4
36
0
2
Order By: Relevance
“…Frozen tissues were ground in liquid nitrogen and nucleic acids extracted by the guanidinium-thiocyanate method. DNA and RNA were fractionated by centrifugation in a CsCl gradient (Maniatis et al, 1982;Terrier et al, 1988). Nucleic acids were also prepared from EJ human cancer cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen tissues were ground in liquid nitrogen and nucleic acids extracted by the guanidinium-thiocyanate method. DNA and RNA were fractionated by centrifugation in a CsCl gradient (Maniatis et al, 1982;Terrier et al, 1988). Nucleic acids were also prepared from EJ human cancer cell line.…”
Section: Methodsmentioning
confidence: 99%
“…Na tireóide normal, há controvérsia quanto à expressão destes genes; Aasland et al 27 encontraram-na elevada inclusive com altos níveis do mRDA do c-myc e do c-fós, contrariamente a outros autores 32,33 que relatam baixos níveis destes mRDA em amostras de tecido tireoidiano normal. Embora a expressão do c-myc e de c-fós esteja elevada em alguns carcinomas tireoidianos, principalmente nos anaplásicos, nenhuma amplificação ou rearranjos destes proto oncogenes foi encontrada e a maioria dos estudos publicados não mostrou importância deles na tumorigênese dos tumores epiteliais da tireóide 27,32,34 .…”
Section: Receptores Associados a Proteínas Nuclearesunclassified
“…Embora a expressão do c-myc e de c-fós esteja elevada em alguns carcinomas tireoidianos, principalmente nos anaplásicos, nenhuma amplificação ou rearranjos destes proto oncogenes foi encontrada e a maioria dos estudos publicados não mostrou importância deles na tumorigênese dos tumores epiteliais da tireóide 27,32,34 . O c-myc parece ter participação importante na proliferação celular, como ocorre na Doença de Graves 33 .…”
Section: Receptores Associados a Proteínas Nuclearesunclassified
“…160,164,165, The abundance of c-myc transcripts may thus be predictive of the outcome of thyroid malignancy. 160,164,165 Where examined, there is a tendency for TSH receptor transcript abundance to correlate negatively with those for c-myc. 164,165 …”
Section: C-myc In Thyroid Cancermentioning
confidence: 99%
“…138,[160][161][162] Immuno-histochemical studies and those of c-myc mRNA indicated an increased expression in thyroid tumor tissue. 111,112,160,162,163 Apparently, the less differentiated a tumor, the greater the abundance of c-myc transcripts. 160,164,165, The abundance of c-myc transcripts may thus be predictive of the outcome of thyroid malignancy.…”
Section: C-myc In Thyroid Cancermentioning
confidence: 99%